The Legitimacy of the Legislative Mandate under the Jordanian Constitution : Defense Law No. (13) of 1992 as a Model): A Comparative Study - Masarweh , سيف; Al-Kasasbeh, عبدالرؤوف (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
Constitutional legislation differed with regard the legislative mandate that allows the legislative authority, and based on a permit from the constitution, to assign some of its legislative powers to the executive authority, as some constitutions, such as the French and Egyptian constitutions, have permitted them within certain considerations and conditions, unlike the Jordanian constitutional legislator. Despite this, the Jordanian constitution included in the text of Article (124) an image that approximates the legislative mandate, which necessitated the issuance of a law called the Defense Law, which was adopted by the study as a model for the legislative authority’s encroachment on the constitution by assigning to the executive authority unusual powers within certain conditions that were not permitted by Article (124); and the assignment of the ordinary legislator some of their competencies to the executive authority under the Defense Law in the field of penal legislation or legislation affecting private life has no basis in the constitution. The study indicated the need to amend the provisions of Article (124) of the constitution to clarify its exact framework, in addition to amending the provisions of the Defense Law, in order to be consistent with the provisions of this article and to withdraw the powers granted under this law from the executive authority, bearing in mind that we have dealt with this law as a model of unconstitutional legislative delegation in Jordanian legislation and not all the forms that exist in the Jordanian legislative system, as there is no room for all of them.